1998
DOI: 10.1097/00000478-199803000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Antibody NB84 in the Differential Diagnosis of Neuroblastoma and Other Small Round Cell Tumors

Abstract: Two hundred fifty-five well-characterized formaldehyde-fixed and paraffin-embedded small round cell tumors mainly from children and young adults including 105 neuroblastomas were immunohistochemically analyzed with the NB84 monoclonal antibody raised to neuroblastoma cells. Most of the undifferentiated neuroblastomas (21 of 22) and all 83 differentiated neuroblastomas reacted with NB84, but none of these tumors were CD99 positive. Compared with synaptophysin, NB84 was more sensitive, although less specific, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(47 citation statements)
references
References 13 publications
2
44
0
1
Order By: Relevance
“…Compared to NB84, we found that synaptophysin, a neuroendocrine marker of well differentiated cells, was positive in 100% of the cases and highly expressed by tumors without potential for recurrence, making synaptophysin a potential marker to predict tumor behavior. Similar findings were also observed by Miettinen 7 and Bozzi. 30 For clinical and pathological use, it would be desirable that the aforementioned adjuvant methods could also provide information related to tumor prognosis, in addition to being easy to perform as well as rapidly assessable and reproducible.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Compared to NB84, we found that synaptophysin, a neuroendocrine marker of well differentiated cells, was positive in 100% of the cases and highly expressed by tumors without potential for recurrence, making synaptophysin a potential marker to predict tumor behavior. Similar findings were also observed by Miettinen 7 and Bozzi. 30 For clinical and pathological use, it would be desirable that the aforementioned adjuvant methods could also provide information related to tumor prognosis, in addition to being easy to perform as well as rapidly assessable and reproducible.…”
Section: Discussionsupporting
confidence: 91%
“…Immunohistochemistry has proved to be a useful adjunctive method for the differential diagnosis of these tumors. 7,8,23 This is particularly true for the identification of lymphomas and leukemia, which are the most frequent members of this group of tumors. However, the diagnosis of neuroblastomas is more complex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oct-4 + cells were detected in all samples (Table 1). Next, these aspirates were double stained with anti-Oct-4 and anti-NB84 (an NB-specific marker) mAbs [40,41]. All BM Oct-4 + cells co-expressed NB84 (range 0.2-1.5%), thus proving their tumor origin (Table 1 and Figure 1B).…”
Section: Identification Of Oct-4 + Cells In Primary Nb Samples and Nbmentioning
confidence: 97%
“…At variance with TEC, bulk tumor cells did not express PSMA, vWF, CD105, HLA-class I or HLA-G ( Figure 6A). Most TECs were found to express the NB-associated markers GD2 [49] NB84 [41], and CD56 [50] ( Figure 6B, 6-8), which were shared by most tumor cells ( Figure 6A). …”
Section: Kinetics Of Human and Mouse Em Formation In Orthotopic Tumormentioning
confidence: 99%